Les enseignants débutants : vécu et transformations - Corinne Ambroise; Marie-Christine Toczek; Sophie Brunot (Éducation et Socialisation)
The first years of teaching often called induction have been extensively studied in particular since the 2000s. Having a strong influence on the fate of the teacher, these early years are part of a long-term process that begins before entering the career. The purpose of the current article is to propose a panorama of the main scientific literature on the career entry with the aim to characterize and reflect the changes associated to this period of the career. Accurately, this paper is based on national and international empirical work on these beginnings in teaching. How do researchers describe the first steps of beginning teachers? Have they identified characteristic phases during these first years of teaching? Are there particular difficulties and specific experience during that period? Are there any typical changes identified during these first years of teaching? These questions will provide a framework to this paper.